Analisis Kontribusi Perusahaan Perkebunan Kelapa Sawit dalam Pemenuhan Kebutuhan Hidup Karyawan di PT Rimbun Sawit Sejahtera Kabupaten Kampar, Riau - Tulfah, Randewi Sagar Sajjida Khairallah; Suswatiningsih, Tri Endar; Ambarsari, Arum (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to find out the form of the company's contribution in meeting the living needs of employees, to analyze how much employee income contributes to the fulfillment of employees' living needs, and to find out the company's and employees' strategies in meeting the living needs of employees at PT Rimbun Sawit Sejahtera, Kampar Regency, Riau. This research will be carried out in August 2024. The method used in this study is a quantitative descriptive method. The samples in this study are BHL employees, SKU employees, and staff taken based on stratified random sampling techniques. The data collection techniques used include observation, interviews, questionnaires, and documentation. The data analysis technique used is descriptive statistical analysis and using a Likert scale. The results of the study show that the form of the company's contribution in meeting the living needs of BHL employees, SKU employees, and staff consists of compensation, facilities, education and training, health and wellbeing, and awards and recognition. The contribution of employee income to the fulfillment of physiological needs was 86.8% for SKU employees and 23.6% for Staff. BHL employees use all of their income for physiological needs because the income they earn is smaller than their expenses. The company's strategy to meet the needs of employees includes the company providing additional compensation, facilities, activity support, appreciation, and opportunities for employees to learn and develop and strategies carried out by employees to meet their life needs, including having a business, a side job, and borrowing from neighbors/family.